Psikoedukasi Parenting dan Perubahan Pemahaman Pengasuhan pada Ibu Balita: Studi Pretest–Posttest - Aditya Dedy Nugraha; Dinda Azizah Fitriani; Lailatul Maghfitoh Azzakiyah (Jurnal Humanitaria Jurnal Ilmu Sosial dan Humaniora, 2026)
Parenting problems in community settings often emerge not only from children's behavior but also from limited parental knowledge in interpreting developmental needs and selecting appropriate responses. This study aimed to describe community-based parenting problems and evaluate a parenting psychoeducation program for mothers of toddlers at Posyandu Matahari I, Kediri. The study used community assessment followed by a one-group pretest-posttest intervention evaluation. Assessment involved observation, interviews, and questionnaires. Twenty mothers completed the pretest and posttest. The psychoeducation covered the first 1000 days of life, stunting prevention, parenting for child development, and prevention of violence against children. The assessment identified practical parenting problems involving eating, sleep, gadget use, difficult behavior, and the use of threats or harsh responses. The mean parenting score increased descriptively from 87.15 before the intervention to 90.55 after the intervention; the low-score category decreased from 10% to 0%, while the high category increased from 40% to 50%. Follow-up monitoring indicated that participants perceived new knowledge and practical benefits. Because no inferential test was available, the findings are interpreted as descriptive improvement rather than statistically significant effectiveness.